POTENSI DAN NILAI EKONOMI CADANGAN KARBON DI HUTAN PENDIDIKAN DAN PELATIHAN PONDOK BULUH - Rikhi Rikardo; Agus Purwoko; Siti Latifah (Program studi Kehutanan USU, 2015)
This study aimed to determine the type of tree vegetation, carbon stocks, and its economic vale in experimental forest of Pondok Buluh, Simalungun District, North Sumatra. It was conducted from April to May 2014. The collection of data used path method, and the sampling technique used Purpose sampling with random start method. The plot size by 20 m × 100 m consist of 10 plots categorized as large plot in observation of trees with diameter > 30 cms and there was small plot within by 5 m × 40 m to observe the tree with diameter 5 cms to < 30 cms. The collection of data performed by non-destructive method with biomass data analysis using allometric models with a carbon content 0f 46% of biomass. The results of study shown that 49 species of trees derived from 25 families. Carbon content stored on observation plots 173,40 tons/ha, and estimation of total carbon stocks 190.737,70 tons. The economic value carbon stock above ground biomass of standing tree in Education Forest of Pondok Buluh around IDR 33.474.466.350,00 to IDR 44.632.621.800,00.